Technical education teachers' perception of higher-order thinking skills and their ability to implement it in Indonesia - Sutarto Hadi Prayitno; Amat Jaedun (Jurnal Pendidikan Vokasi, 2022)
World Economic Forum's report (2020) reported that the top five out of 10 skills needed by employers in 2025 are (1) analytical thinking and innovation, (2) active learning and learning strategies, (3) complex problem solving, (4) critical thinking and analysis, and (5) creativity, originality, and initiative. These skills thrive workers entering the Fourth Industrial Revolution (4IR) and are the core of Higher Order Thinking Skills (HOTS). Parallelly, educationists conclude that teaching students with HOTS is a must, but the challenge is how to do it effectively. This study's objectives were to know vocational and technical teachers' perception of HOTS and their ability to teach HOTS in their classrooms. The study population was State Vocational and Technical Senior High School (SMKN) in Yogyakarta Special Region (DIY) and Central Java Province (CJP) in Indonesia. The sample was determined by quota technique sampling and came up with SMKN 2 Yogyakarta in DIY and SMKN 2 Klaten, and SMKN Magelang in CJP. Collecting data technique used closed- and open- questionnaires and documentation. Data analysis used statistical descriptive and qualitative description. Research findings revealed that teachers' perception of HOTS was very positive, while their ability to integrate HOTS concepts in their lesson plans and to implement them in the classroom still has significant difficulties.